Analisis Manajemen Sumber Daya Manusia Pada Lembaga Pendidikan Islam di MAN 2 Kota Sukabumi - Fitri Julianti; Silvia Sri Rahayu; Wilma Maulia Nimatullah; Adi Rosadi (CV Edujavare Publishing, 2024)
This research aims to investigate human resource management practices at MAN 2 Sukabumi City, Particularly about Islamic education. With the use of qualitative research techniques, in-depth interviews were used to gather data. with teaching staff and school management, direct observation combined with relevant document analysis. The study's findings indicate that MAN 2 Sukabumi City faces various challenges in human resource management, including in the recruitment, training, development and retention of teaching staff. Nonetheless, some effective practices have been found, including regular training programs, career guidance, and fostering an inclusive work environment. The implication of this research is the need to increase awareness and commitment in managing human resources in Islamic educational institutions, as well as the need for support from local governments and related stakeholders. These findings can provide valuable insights for other Islamic educational institutions strive to improve teaching standards and cultivate your people resources